The agreement between automated breast ultrasound (ABUS) and digital breast tomosynthesis (DBT) in detecting architectural distortions among patients undergoing breast Imaging. - Ismail, Nur Zainatul Izzah Md (2023)
Background: Breast cancer is the leading cancer affecting women, globally. Early detection is vital to improve the survival rate and reduce morbidity. Architectural distortion is one of the early findings in breast cancer, however it is difficult to visualize especially in a dense breast. It is the third most common presentation of breast cancer, where 44.2% of architectural distortion is often malignant. Automated breast ultrasound (ABUS), enables three-dimensional image giving better visualization of the breast tissues. It is non operator dependent with reproducible images. In view of its non- ionizing feature, it is a better choice for younger patient as well as patients with dense breast. The aim of this study is to explore the ability of detecting architectural distortion as a potential substitute for digital breast tomosynthesis (DBT) in breast cancer screening for the young or pregnant women, and those with dense breasts. Methods: This is a cross sectional study done in Hospital Unversiti Sains Malaysia, Kubang Kerian, Kelantan. Patients with architectural distortion detected in DBT were subjected to ABUS. The images were reviewed, examined for the presence of architectural distortions. A total of 37 architectural distortions were studied, involving 37 of women. The agreement between mammography and ABUS in detecting architectural distortions were tested using Kappa agreement test. Results: There is a moderate agreement of straightening of parenchyma edges between DBT and ABUS with kappa value 0.421 (p=0.008), and moderate agreement in spiculation, kappa value 0.525 (p=0.001). Slight agreement in detecting focal retraction, kappa value 0.183 (p =0.054). Conclusion: ABUS is a good tool in detecting architectural distortion which demonstrated moderate agreement with DBT. It can be considered as an adjunct to DBT as well as, initial screening for young women.